Optimal Design of Integrated Energy Supply System for Continuous Greenhouse Effect: A Study on Carbon Emission and Operational Cost - Tian, Chongyi; Shao, Zhuliang; Wang, Ruiqi; Yan, Yi; Wang, Xuerui; Ren, Ang (Frontiers in Energy Research, 2022)
The cultivation of crops in greenhouses is well established in China. However, the greenhouse climate is complex, rendering it difficult to analyze the greenhouse load and control the energy supply system. It is important to ensure the optimal design of greenhouse operation to enable optimal crop growth and maintain low operation costs for improving the greenhouse crop production efficiency and economic benefits. To reduce the energy consumption , we propose a new integrated energy supply system. This system uses a combined cooling, heating and power system, and an air source heat pump. A two-stage integrated optimization model of the integrated energy supply system was built, with “minimum average daily economic cost” and “maximum CO2 emission reduction rate (ERR)” as the objectives in the first stage. The characteristics of the countryside were taken into consideration for optimizing the capacity of the combined cooling, heating and power supply, energy storage and air source heat pump. In the second stage, the objectives were “maximum annual operating saving rate (OSR)”, “maximum CO2 emission reduction rate”, and “maximum primary energy saving rate (PESR)”. The capacity of the equipment designed in the first stage is used as the constraint to optimize the operating output of the combined cooling, heating and power supply, air source heat pump. Finally, a greenhouse is used as a prototype to carry out simulation calculations for two typical days in summer and winter to verify the effectiveness of this method. The simulation results showed that after the first stage of optimization, the average daily operating cost was significantly lower and the CO2 emission rate was reduced by 49.53%. After the second stage, annual operating saving rate, CO2 emission reduction rate, and primary energy saving rate were 39.51, 48.88, and 27.57% for a typical summer day and 52.96, 50.18, and 50.13% for a typical winter day, respectively. Therefore, compared to the existing energy supply systems, the integrated energy supply system and the integrated optimization design of the system could effectively avoid energy wastage, significantly improve the degree of match between the system design and operation, reduce operating cost, and reduce CO2 emission.